# y-2x=-5

3y-x=5

In the top equation:
1) y=2x -5
Put that in the second equation
3( ) -x =5
solve for x, then put that value of x back in to 1) to solve for y.

So would it be:
3(2x-5)=5?

would it?PLz help me bob and margie!

## To solve the system of equations y-2x=-5 and 3y-x=5, you first need to rearrange one of the equations to solve for one variable in terms of the other. Let's rearrange the first equation, y-2x=-5, to solve for y:

y = 2x - 5

Now, substitute this expression for y into the second equation, 3y - x = 5:

3(2x - 5) - x = 5

Simplify the equation:

6x - 15 - x = 5

Combine like terms:

5x - 15 = 5

Next, isolate the variable x by moving the constant term to the other side:

5x = 5 + 15

5x = 20

Now, divide both sides of the equation by 5 to solve for x:

x = 20/5

x = 4

Once you have found the value of x as 4, substitute this value back into the expression for y:

y = 2x - 5

y = 2(4) - 5

y = 8 - 5

y = 3

Therefore, the solution to the system of equations is x = 4 and y = 3.